2016
DOI: 10.1016/j.burns.2015.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Burns in Baghdad from 2003 to 2014: Results of a randomized household cluster survey

Abstract: Purpose Civilians living amid conflict are at high-risk of burns. However, the epidemiology of burns among this vulnerable group is poorly understood, yet vital for health policy and relief planning. To address this gap, we aimed to determine the death and disability, healthcare needs and household financial consequences of burns in post-invasion Baghdad. Methods A two-stage, cluster randomized, community-based household survey was performed in May of 2014 to determine the civilian burden of injury from 2003… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 38 publications
0
10
0
1
Order By: Relevance
“…36 This high rate could be described as an epidemic. It arose from the security instability all over the country, 37 added to the status of thousands of displaced families where 16% had no ordinary facilities for cooking and personal warming, a situation that increased the risk of burn accidents. 38…”
Section: Resultsmentioning
confidence: 99%
“…36 This high rate could be described as an epidemic. It arose from the security instability all over the country, 37 added to the status of thousands of displaced families where 16% had no ordinary facilities for cooking and personal warming, a situation that increased the risk of burn accidents. 38…”
Section: Resultsmentioning
confidence: 99%
“…The findings in our burn center when compared with developed countries showed that LA50 and survival of burn patients were less denoting to an urgent necessity for prompt attention to promote current policies in public health issue and to decrease the mortality rate 25 . In Baghdad, Iraq, burn injury is still a prevalent health issue with an increasing trend imposing a household financial load, high mortality rate and disability occurring after burn injury mandating the need for planning burn prevention and care program 26 .…”
Section: Discussionmentioning
confidence: 99%
“…While we are unable to infer the epidemiology of injury in the population from these hospital-based data, the findings support other studies from Iraq that suggest unintentional injuries predominate in populations affected by prolonged insecurity. [19][20][21] A population-based survey of injuries in Baghdad from 2003-2014 reported that falls, road traffic crashes, and mechanical injuries were more common than all violence-related injuries combined. 20 The authors concluded that deterioration of infrastructure, changes in safe behavior, and a lack of injury prevention and control programs contribute to this epidemiology.…”
Section: Discussionmentioning
confidence: 99%